Disease-Modifying Drugs and Breastfeeding in Multiple Sclerosis: A Narrative Literature Review - Capone, Fioravante; Albanese, Angela; Quadri, Giorgia; Di Lazzaro, Vincenzo; Falato, Emma; Cortese, Antonio; De Giglio, Laura; Ferraro, Elisabetta (Frontiers in Neurology, 2022)
Pregnancy-related issues in women with multiple sclerosis (MS) have been receiving increasing attention, with particular interest for the use of disease-modifying therapies (DMTs) before conception, during pregnancy, and postpartum, including breastfeeding. The risk of relapse is higher in the early postpartum period, especially in cases of significant disease activity prior to pregnancy, and thus treatment resumption and/or switching strategies might be necessary. Moreover, breastfeeding provides unmatched health benefits for babies and mothers, and is recommended as the best source of nutrition for infants. Furthermore, a protective role of breastfeeding on MS disease course has not been fully demonstrated and it remains debatable. At the same time, a source of concern is the potential transfer of DMTs into breastmilk and the resulting infant exposure. The use of most DMTs is unlicensed during breastfeeding mainly due to the limited data available on the excretion in human milk and on the effects on infants’ exposure. Consequently, women have to face the difficult challenge of choosing between breastfeeding and DMT resumption. The present narrative review summarizes and discusses the available evidence on the safety of DMTs during breastfeeding and the relative approved labels. At the time of diagnosis of MS, specific counseling should be offered to women of childbearing age, making them aware of the possible therapeutic options and their impact on pregnancy and breastfeeding. Women can be encouraged to breastfeed, if clinically feasible, following a review of their medications and clinical status, with a personalized approach.